CD4+ Natural Killer T Cells Potently Augment Aortic Root Atherosclerosis by Perforin- and Granzyme B-Dependent Cytotoxicity. Issue 2 (16th January 2015) - Li, Yi; To, Kelly; Kanellakis, Peter; Hosseini, Hamid; Deswaerte, Virginie; Tipping, Peter; Smyth, Mark J.; Toh, Ban-Hock; Bobik, Alexander; Kyaw, Tin
<x xml:space="preserve">Abstract</x> Rationale: CD4+ natural killer T (NKT) cells augment atherosclerosis in apolipoprotein E–deficient (ApoE)−/− mice but their mechanisms of action are unknown. Objectives: We investigated the roles of bystander T, B, and NK cells; NKT cell–derived interferon-γ, interleukin (IL)-4, and IL-21 cytokines; and NKT cell–derived perforin and granzyme B cytotoxins in promoting CD4+ NKT cell atherogenicity. Methods and Results: Transfer of CD4+ NKT cells into T- and B-cell–deficient ApoE−/−Rag2−/− mice augmented aortic root atherosclerosis by ≈75% that was ≈30% of lesions in ApoE−/− mice; macrophage accumulation similarly increased. Transferred NKT cells were identified in the liver and atherosclerotic lesions of recipient mice. Transfer of CD4+ NKT cells into T-, B-cell–deficient, and NK cell–deficient ApoE−/−Rag2−/−γC−/− mice also augmented atherosclerosis. These data indicate that CD4+ NKT cells can exert proatherogenic effects independent of other lymphocytes. To investigate the role of NKT cell–derived interferon-γ, IL-4, and IL-21 cytokines and perforin and granzyme B cytotoxins, CD4+ NKT cells from mice deficient in these molecules were transferred into NKT cell–deficient ApoE−/−Jα18−/− mice. CD4+ NKT cells deficient in IL-4, interferon-γ, or IL-21 augmented atherosclerosis in ApoE−/−Jα18−/− mice by ≈95%, ≈80%, and ≈70%, respectively. Transfer of CD4+ NKT cells deficient in perforin or granzyme B failed to augment atherosclerosis. Apoptotic cells, necrotic cores, and proinflammatory VCAM-1 (vascular cell adhesion molecule) and MCP-1 (monocyte chemotactic protein) were reduced in mice receiving perforin-deficient NKT cells. CD4+ NKT cells are twice as potent as CD4+ T cells in promoting atherosclerosis. Conclusions: CD4+ NKT cells potently promote atherosclerosis by perforin and granzyme B–dependent apoptosis that increases postapoptotic necrosis and inflammation.